2020
DOI: 10.1038/s41388-020-1162-2
|View full text |Cite
|
Sign up to set email alerts
|

FAK signaling in cancer-associated fibroblasts promotes breast cancer cell migration and metastasis by exosomal miRNAs-mediated intercellular communication

Abstract: Cancer-associated fibroblasts (CAFs) are activated fibroblasts that constitute the major components of tumor microenvironment (TME) and play crucial roles in tumor development and metastasis. Here, we generated fibroblast-specific inducible focal adhesion kinase (FAK) knockout (cKO) mice in a breast cancer model to study potential role and mechanisms of FAK signaling in CAF to promote breast cancer metastasis in vivo. While not affecting primary tumor development and growth, FAK deletion significantly suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 50 publications
1
87
0
Order By: Relevance
“…The link between FAK and breast cancers is strongly suggested by a number of reports showing that FAK gene is amplified and overexpressed in a large fraction of breast cancer specimens [ 39 ]. Recently, it was shown that, while not affecting primary tumor development and growth, FAK deletion significantly suppressed breast cancer metastasis in vivo [ 40 ]. Another study demonstrated that knockdown of FAK expression in TNBC cells or the treatment of TNBC cells with a FAK inhibitor followed by co-culture with cytokine-induced killer (CIK) cells increased the death of TNBC cells, suggesting that FAK plays an important role in sensitizing tumor cells to CIK cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The link between FAK and breast cancers is strongly suggested by a number of reports showing that FAK gene is amplified and overexpressed in a large fraction of breast cancer specimens [ 39 ]. Recently, it was shown that, while not affecting primary tumor development and growth, FAK deletion significantly suppressed breast cancer metastasis in vivo [ 40 ]. Another study demonstrated that knockdown of FAK expression in TNBC cells or the treatment of TNBC cells with a FAK inhibitor followed by co-culture with cytokine-induced killer (CIK) cells increased the death of TNBC cells, suggesting that FAK plays an important role in sensitizing tumor cells to CIK cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, tumor cell-derived exosomal miRNAs are highly diverse and are capable of differentiating NFs into CAFs through a variety of signaling pathways. Exosomal miRNAs from cancer cells elicit a parenchymal signaling response at the receptor site and effectively inducing fibroblast activation, such as α-smooth muscle actin (α-SMA), fibroblast growth factor 2 (FGF2) and fibroblast activating protein (FAP) expression [98][99][100]. Matrix composed of CAFs is conducive to the proliferation and migration of tumor cells.…”
Section: Reshaping Ecm To Promote Tumor Progressionmentioning
confidence: 99%
“…This chemoresistance was found to be due to decreased secretion of TGF-β by CAFs, which led to increased activation of STAT3 signaling 49 . The importance of FAK in CAFs was further studied through the use of a fibroblast-specific FAK knockout mouse model in which the loss of FAK in CAFs led to decreased breast cancer metastasis 50 . This study found that exosomes isolated from FAK-null CAFs contained elevated levels of the tumor-suppressing microRNAs miR-16 and miR-148a 50 , suggesting that FAK expression in CAFs may play a role in exosome-mediated regulation of cancer cell proliferation.…”
Section: Cancer-associated Fibroblasts (Cafs) and Ecmmentioning
confidence: 99%